Projeto de um módulo de registro e monitoramento da evasão para o sistema acadêmico da Universidade Federal do Triângulo Mineiro - SISCAD - ALVES, Moysés de Oliveira Pereira (2018)
This academic work presents a proposal for the development of a new module for the Academic Control System (SISCAD) of the Federal University of the Triângulo Mineiro, which aims to manage the control of requests for cancellations and cancellations of enrollment, evasion, according to the regulations and guidelines of the institution, in addition, seeks to apply the operationalization, data collection by means of a questionnaire in the act of requesting evasion and subsequent disclosure of the results through reports regarding the reasons for evasion recorded by the students, thus providing data to the coordinators of the undergraduate courses and administrators of the institution. It is hoped that this proposal, as a technological product, will contribute to the system of management, control and prevention of student turnover and as a form of subsidy for future decision-making.